The Case Study Method: A Paradoxical Research Specificity and Multiplicity - Babatunde Covenant Olugbenga; Muhammad Ridwan (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2025)
The case study method remains one of the most debated yet widely employed qualitative research strategies across disciplines. Its strength lies in its capacity to explore complex phenomena within real-life contexts, yet it is often critiqued for lacking generalizability and methodological rigor. This paper interrogates the paradoxical nature of the case study method, examining how it simultaneously embodies research specificity through in-depth focus on a single or bounded case and multiplicity by offering rich, transferable insights applicable across contexts. Drawing on key theoretical perspectives and methodological debates, the study explores the dual identity of the case study as both a unit of analysis and a research design. Through illustrative examples from social sciences and humanities, the paper reveals how the method’s flexibility challenges rigid research classifications while enabling profound contextual understanding. The conclusion advocates for a more nuanced appreciation of the case study method’s potential, calling for clearer methodological frameworks that embrace its paradoxes rather than obscure them.